The application of nuclear physics processesfor diamond detection within kimberlite - Mampe, P W (2015)
Mineral-PET (Positron Emission Tomography) is a new concept envisaged to revolutionize diamond-mining operations. The idea is that diamond inclusions may be detected at an early stage. This allows for rejection of barren material from the processing stream, which greatly reduces the costs. The diamond recovery may also be more efficient. In fact, not only the presence but also the size and relative position of the diamond inclusion in the host kimberlite rock may be determined. This allows for grading and differentiated extraction techniques, which may protect larger diamonds. The process involves the use of the (y,n) interaction at the Giant Dipole Resonance energy of carbon to produce a radioactive carbon-11 PET isotope to label the presence of possible diamonds. This is followed by the use of an analogue of the medical Positron Emission Tomography (PET) diagnostic method to detect the evidence of diamonds in the kimberlite. The Mineral-PET process has an activation stage. to generate the 11C positron-emitting isotope in the kimberlite, and a detection stage, where the occurrence of hot-spots in the PET signal may distinguish diamondifcrous from barren kimberlite. This dissertation makes a contribution in the detection part. Specifically, experimental work has been done on absorption length measurements for kimberlite, as well as a study of the noise reduction capacity of the co-incident detection technique. The former measurement was used as input for computational simulations. The latter measurement \\as part of the verification of the feasibility calculation for the system as a whole. Computer modeling by Monte Carlo methods ha been used in order to simulate the Mineral-PET system. In this work, the aspects of the Mineral-PET system that were simulated relate to the efficiency of the detectors and the absorption length of radiation by the kimberlite. === Thesis (M.Sc. (Applied Radiance Science ) North-West University, Mafikeng Campus, 2013